(untitled) (SCIENCE TIME JOURNAL, 2025)
this article explores methods of teaching English to journalism students by integrating the linguistic, stylistic, and structural features of journalistic genres. It examines how genre-specific tasks enhance language competence, critical thinking, and professional writing skills. The study offers pedagogical strategies aligning language instruction with the practical demands of journalistic practice in multimedia and cross-cultural communication contexts.